Women Educators, Leaders and Activists : Educational Lives and Networks 1900-1960 - Fitzgerald, Tanya; Smyth, Elizabeth M.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This collection traces women educators' professional lives and the extent to which they challenged the gendered terrain they occupied. The emphasis is placed on women's historical public voices and their own interpretation of their'selves' and'lives' in their struggle to exercise authority in education.
Keywords: History; History, Modern; Social history; School management and organization; School administration; Education -- History; Gender identity in education; Sociology; Sex (Psychology).; Gender expression; Gender identity; History; Social History; Gender and Education; Gender Studies; History of Education; Administration, Organization and Leadership; Modern History